Sperm Parameters and Reproductive Hormones Among Male Sudanese Worker Exposed to High Occupational Heat - Ahmed PhD, Shams Eldin Mohamed; Babikir MD, Saeed; Hasan MD, Badr Eldin; MD, Mustafa Omran; MD, Mohamed Elimam. (مجلة الجزيرة للعلوم الصحية; مجلد 7 عدد 2 (2011), 2011)
Introduction: The hormonal function of the human testicle is temperature dependant. It requires a temperature 2 – 4 C˚ below body temperature. The frequency and time of heat exposure are capable of producing reversible or irreversible changes in human spermatogensis. Objective : the aim of this study is to reconfirm or refute the previously tested hypothesis that the occupational heat exposure reduces both sperm output and quality in fertile men due to increases of scrotal and testicular temperature. Materials and methods : Sperm quality was examined in 216 Sudanese workers in sugar factories, Bakeries and Khartoum Foundry center, their ages between 18-54 years old. A scrotal temperature ranged between 38.9-41 C˚ and heat exposure for 1 to 24 years were recorded. A 102 age and place-matched unexposed workers who had scrotal temperature range between 32-34 C˚ was used as a control group. Venous blood (5-10 ml) and semen samples by masturbation were collected from them. Serum was prepared and analyzed for reproductive hormones by RIA techniques. Semen samples were analyzed by Computer Assisted Sperm Analysis (CASA) method. Results: The results of this study indicated that sperms (count, motility and morphology) were assessed in both groups. The sperm density, motility and morphology were significantly affected in the test group P.value (000). In the test group it was found that the longer the duration of exposure the more significant is the decline in all sperm parameters, and those who were exposed for more than 10 years may develop azoospermia. 20 volunteers were found to have primary infertility and 8 to have secondary infertility. FSH significantly increased in the azoospermic and oligospermic groups, while the other hormones, LH, Testosterone and Prolactin, remained within the normal range levels. High testicular temperature impaired spermatogenesis leading to oligozoospermia, asthenozoospermia, teratzoospermia and azoospermia. Therefor, the long term effects of hyperthermia adversely affect the sperm quantity and quality. Long term testicular hyperthermia may lead to primary and secondary infertility. The fasting baseline of FSH levels is negatively proportional with the sperm density. Conclusion : These results support the hypothesis that increases in heat exposure are associated with reduced semen quality.